A model of qardhul hassan for university staff in Malaysia - Hanudin Amin; Faizah Panggi (Emerald, 2025)
This study investigated drivers that explain qardhul hassan financing acceptance in Malaysia involving staff of two universities namely A in East Malaysia and B in West Malaysia. Design/methodology/approach – The attitude-social influence-self-efficacy (ASE) model was tested to examine 422 respondents’ acceptance using SPSS 27. Findings – The study confirmed the significance of all tested hypotheses, with attitude playing a key mediating role. Further, this study uncovered significant results of relative advantage and Islamic debt collection policy, offering novel contributions to this discipline. Research limitations/implications – The generalization of the findings generated was limited to the context concerned and the limited variables tested. Practical implications – The results offer a directive for universities to offer qardhul hassan in the future to attract demand and acceptance. Originality/value – This study introduced a modified ASE called the QH-ASE framework to analyze its adoption, adaptability and impact on qardhul hassan financing usefulness.